Mechanical and thermal properties of phase change energy storage concrete. (June 2020) - Zhang, Yichao; Zhang, Zhongren; Zhou, Jinghai; Wang, Ying
Abstract: Phase change energy storage particles have excellent thermal properties. The phase change energy storage concrete prepared by adding phase change energy storage particles to concrete has excellent mechanical properties and thermal properties of concrete. Choosing appropriate phase change materials and mix proportion can effectively reduce the energy consumption of concrete buildings on the premise of meeting the requirements of compressive strength. In this paper, the mechanical and thermal properties of phase change energy storage concrete are reviewed, and the existing problems are analyzed, and the future development trend is prospected.